Japanese Astrometry Satellite Mission for Infrared Exploration - Gouda, Naoteru; Tsujimoto, Takuji; Kobayashi, Yukiyasu; Nakajima, Tadashi; Yasuda, Naoki; Matsuhara, Hideo (Astrophysics and space science, 2002)
JASMINE is the name of a Japanese infrared (K-band) scanning astrometric satellite. JASMINE (I and/or II-project) is planned to be launched between 2013 and 2017 and will measure parallaxes and proper motions with the precision of 10μas at K 12 - 15 mag. JASMINE will observe a few hundred million stars belonging to the disk and the bulge components of our Galaxy, which are hidden by the interstellar dust extinction in optical bands. Furthermore, JASMINE will also obtain photometry of stars in K, J and H-bands. The main objective of JASMINE is to study the most fundamental structure and evolution of the disk and the bulge components of the Milky Way Galaxy.[PUBLICATION ABSTRACT]